The influence of an afternoon nap on the endurance performance of trained runners - Blanchfield, A. W.; Lewis-Jones, T. M.; Wignall, J. R.; Roberts, J. B.; Oliver, S. J. (European Journal of Sport Science, 2018)
The effectiveness of a nap as a recovery strategy for endurance exercise is unknown and therefore the present study investigated the effect of napping on endurance exercise performance. Eleven trained male runners completed this randomised crossover study. On two occasions, runners completed treadmill running for 30 min at 75% O2max in the morning, returning that evening to run for 20 min at 60% O2max, and then to exhaustion at 90% O2max. On one trial, runners had an afternoon nap approximately 90 min before the evening exercise (NAP) whilst on the other, runners did not (CON). All runners napped (20 ± 10 min), but time to exhaustion (TTE) was not improved in all runners (NAP 596 ± 148 s vs. CON 589 ± 216 s, P = .83). Runners that improved TTE after the nap slept less at night than those that did not improve TTE (night-time sleep 6.4 ± 0.7 h vs. 7.5 ± 0.4 h, P < .01). Furthermore, night-time sleep predicted change in TTE, indicating that runners sleeping least at night improved TTE the most after the nap compared to CON (r2 = -0.76, P = .001). In runners that improved TTE, ratings of perceived exertion (RPE) were lower during the TTE on NAP than CON compared to runners that did not improve (-0.4 ± 0.6 vs. 0 ± 0, P = .05). Reduced exercising sense of effort (RPE) may account for the improved TTE after the nap. In conclusion, a short afternoon nap improves endurance performance in runners that obtain less than 7 h night-time sleep.